PENENTUAN KEY PERFORMACE INDICATORS PIMPINAN UNIT SATUAN KERJA DENGAN KONSEP BALANCED SCORECARD - Endang Dwi Retnani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
Methodology used in this research was qualitative method with case study approach. The method was chosen in order to study in more detail all steps applied in determination Key Performance Indicators by each responsible manager unit within the Private University “STIESIA” based on BSC for boosting the manager to do continuous improvement innovation. Steps used by responsible manager units of Private University “STIESIA” in determination key performance indicators based on BSC consisted of (1) Strategy Good Perspective;(2) Strategy Map;(3) Strategy Management Goals;(4) Strategic Management Scorecards, and (5) Strategic Academic Scorecards.With the establishment of Management Scorecard and Strategic Academic Scorecards, it was an importance step performed by all responsible manager units in Private University “STIESIA” for issuing focused strategy of continuous improvement innovation both in academic and non-academic affairs as to achieve the goal of the Private University “STIESIA” as the best institution. Further steps needed by the top managements of the Private University “STIESIA” - that is the Board of Foundation and the Dean of the Private University “STIESIA”, are to establish guideline for determining yearly work plan and measuring work performances.The guidelines were established based not only on financial perspective,but also on non-financial perspectives that were consisted of customer satisfaction,internal business process and learning and growth factors.In addition,in order to be able to achieve an objective performance measurement for each responsible manager unit,therefore it is necessary to apply a weighted proporsion for each above perspective.